Fine spectra of tridiagonal Toeplitz matrices - Altun, M.; Bilgiç, H. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
UDC 514.74 The fine spectra of n-banded triangular Toeplitz matrices and (2n+1)-banded symmetric Toeplitz matrices were computed in ( M. Altun, Appl. Math. and Comput. – 2011. – 217. – P. 8044 – 8051) and ( M. Altun, Abstr. and Appl. Anal. – 2012. – Article ID 932785). As a continuation of these results, we compute the fine spectra of tridiagonal Toeplitz matrices. These matrices are, in general, not triangular and not symmetric.